Study of Culture and Sensitivity Pattern In Urinary Tract Infections in A Tertiary Care Center in Nepal - Binod Chapagain; Parshal Bhandari; Binod Aryal (Medical Laboratory Technology Journal, 2018)
The main purpose of this study was to find out the causative agents of urinary tract infections (UTI) and their culture and antibiotic sensitivity in patients visiting Tribhuvan University and Teaching Hospital (TUTH). A retrospective study conducted among 155 patients, aged from 25-50 years with culture-positive UTI, who visited TUTH from 1st April 2017 to 30th September 2017. A culture of midstream urine was done to find out causative agents and their antibiotic sensitivity performed. Data were evaluated using Microsoft Excel 2016. Female were more affected than males. Escherichia coli (E. coli) was the most common microbes causing UTI in 53% patients. Most of the isolates on culture were Multi-Drug Resistant (MDR) strains to comprise 52%. Of the total gram-negative organisms, 33.9% were Extended Spectrum β-lactamase (ESBL) producers, and 3.57% were Metallo β-lactamase (MBL) producers. 29.41% of Staphylococcus were resistant to methicillin. E.coli is the most common organism causing UTI among adults. Multidrug-resistant has appeared alarming with resistant to most of the first line antibiotics.